Specific Characteristics of Organizing the Training Plan of Weekly Micro cycles of 14-15-Year-Old Freestyle Athletes. - Sultonov Shukhrat Nurmakhamatovich (Genius Journals, 2023)
In this article, the method of effective organization of training plan in weekly microcycles of 14-15-year-old freestyle wrestlers training in the primary training group is developed
Keywords: Free wrestlers; training processes; organization